Do Conceptions of Learning Predict Language Learning Strategies? Evidence from Indonesian EFL Learners - Dairabi Kamil (Indonesian Research Journal in Education |IRJE|, 2021)
Research has shown that information on students’ conceptions of learning (COL) and their language learning strategies (LLS) are beneficial for understanding certain recurring phenomena of foreign language learning and outcomes. However, these two constructs have been separately studied from each other. This study sought to fill this void by investigating the relationship between the constructs and the extent to which COL predicts LLS. Data were collected by administering the Conceptions of Learning Inventory (COLI) and Strategy Inventory for Language Learning (SILL) to 210 pre-service EFL teachers at an English department of a state higher education institution in Indonesia. Data were analyzed using the nonparametric Spearma’s-Rho test and Regression Tree (RT) analysis technique. The results show statistically significant positive correlations between the two constructs. Further analyses show that COL, to some extent, predicted LLS.